Splenic Vein Thrombosis Following Pancreas Transplantation: Identification of Factors That Support Conservative Management. Issue 11 (14th August 2017) - Harbell, J. W.; Morgan, T.; Feldstein, V. A.; Roll, G. R.; Posselt, A.; Kang, S.‐M.; Feng, S.; Hirose, R.; Freise, C. E.; Stock, P.
Abstract : Prophylaxis for graft portal/splenic venous thrombosis following pancreas transplant varies between institutions. Similarly, treatment of venous thrombosis ranges from early re‐exploration to conservative management with anticoagulation. We wished to determine the prevalence of graft splenic vein (SV) thrombosis, as well as the clinical significance of non‐occlusive thrombus observed on routine imaging. Records of 112 pancreas transplant recipients over a 5‐year period at a single center were reviewed. Venous thrombosis was defined as absence of flow or presence of thrombus identified in any part of the graft SV on ultrasound. Thirty patients (27%) had some degree of thrombus or absence of flow in the SV on postoperative ultrasound. There were 5 graft losses in this group. Four were due to venous thrombosis, and occurred within 20 days of transplant. All patients with non‐occlusive partial SV thrombus but normal arterial signal on Doppler ultrasound were successfully treated with IV heparin followed by warfarin for 3–6 months, and remained insulin independent. Findings of arterial signal abnormalities, such as absence or reversal of diastolic flow within the graft, require urgent operative intervention since this finding can be associated with more extensive thrombus that may lead to graft loss. Abstract : This review of long‐term outcomes of graft venous thrombosis following pancreas transplant identifies imaging and clinical characteristics of nonocclusive thromboses that support conservative management.